Direct measurement of the pulse duration and frequency chirp of seeded XUV free electron laser pulses. (8th January 2018) - Azima, Armin; Bödewadt, Jörn; Becker, Oliver; Düsterer, Stefan; Ekanayake, Nagitha; Ivanov, Rosen; Kazemi, Mehdi M; Lazzarino, Leslie Lamberto; Lechner, Christoph; Maltezopoulos, Theophilos; Manschwetus, Bastian; Miltchev, Velizar; et al.
Abstract: We report on a direct time-domain measurement of the temporal properties of a seeded free-electron laser pulse in the extreme ultraviolet spectral range. Utilizing the oscillating electromagnetic field of terahertz radiation, a single-shot THz streak-camera was applied for measuring the duration as well as spectral phase of the generated intense XUV pulses. The experiment was conducted at FLASH, the free electron laser user facility at DESY in Hamburg, Germany. In contrast to indirect methods, this approach directly resolves and visualizes the frequency chirp of a seeded free-electron laser (FEL) pulse. The reported diagnostic capability is a prerequisite to tailor amplitude, phase and frequency distributions of FEL beams on demand. In particular, it opens up a new window of opportunities for advanced coherent spectroscopic studies making use of the high degree of temporal coherence expected from a seeded FEL pulse.